1992
DOI: 10.1002/fut.3990120205
|View full text |Cite
|
Sign up to set email alerts
|

Hedge period length and Ex‐ante futures hedging effectiveness: The case of foreign‐exchange risk cross hedges

Abstract: Support from the DePaul College of Commerce summer research grants program is gratefully 'Data are obtained from the IMM Yearbook, the CRB Commodity Yearbmk, and The Wall Street 'For a discussion of the various theoretical drawbacks of the mean-variance (risk-minimizing) acknowledged. Journal for the time period August 31, 1973 to December 31, 1985.hedging approach, refer to Levy and Sarnat (1984) and Marmer (1986).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 21 publications
2
46
0
2
Order By: Relevance
“…This suggests that there is more market uncertainty at short scales or in a statistical sense that there is greater noise, increasing the difficulty of measuring the hedge ratio accurately, Benet (1992). However, by the second scale (2 − 4 day horizon) the effectiveness is greater than that found using the original data, and then increases to a maximum of 0.98 (variance reduction) or 0.88 (VaR reduction) at long scales.…”
Section: Dynamic Scale Dependent Hedgingmentioning
confidence: 89%
See 1 more Smart Citation
“…This suggests that there is more market uncertainty at short scales or in a statistical sense that there is greater noise, increasing the difficulty of measuring the hedge ratio accurately, Benet (1992). However, by the second scale (2 − 4 day horizon) the effectiveness is greater than that found using the original data, and then increases to a maximum of 0.98 (variance reduction) or 0.88 (VaR reduction) at long scales.…”
Section: Dynamic Scale Dependent Hedgingmentioning
confidence: 89%
“…In the context of hedging, a limited number of studies, including Ederington (1979); Hill and Schneeweis (1982); Malliaris and Urrutia (1991);Benet (1992); Geppert (1995), have demonstrated an increase in hedging effectiveness for longer horizons, by matching the frequency of the data with the hedging horizon. However, out-of-sample, Malliaris and Urrutia (1991); Benet (1992) found a lack of stability in the hedging effectiveness for longer horizons. More recently, Chen et al (2004) demonstrated, using subsampled data, that both the hedge ratio and effectiveness tend to increase with the length of time horizon.…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest greater levels of noise in high frequency data, creating difficulty in measuring the hedge ratio accurately (Benet, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…However, Benet (1992) found a lack of stability in the effectiveness at longer horizons out-of-sample, due to the sample reduction problem. To overcome the problem of reduced data at longer horizons, wavelet multiscaling techniques have been adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation